Association Between Gamma-Glutamyl Transferase and Mild Cognitive Impairment in Chinese Women - Tang, Zhaoyang; Chen, Xueyu; Zhang, Wenran; Sun, Xiangfu; Hou, Qingzhi; Li, Yuejin; Feng, Xia; Chen, Yanru; Lv, Jian; Ji, Long; Ding, Guoyong; Li, Dong (Frontiers in Aging Neuroscience, 2021)
Background: Dementia, as a global public health problem, is becoming increasingly serious. As a precursor of dementia, mild cognitive impairment (MCI) plays an important role in the diagnosis and prevention of dementia. Recent studies have found a correlation between gamma-glutamyl transferase (GGT) levels and cognitive function in men. The relationship between GGT levels and cognitive function in women remains unclear because GGT activity and expression differ between the sexes. Method: We recruited a total of 2,943 Chinese women from Jidong and Taian in 2019. We grouped the participants according to GGT levels, diagnosed MCI using the Montreal Cognitive Assessment (MOCA) scale, and modeled the study outcomes using logistic regression to explore the relationship between GGT level and MCI. We also analyzed the interaction of obesity, sleep duration, and hyperuricemia with GGT in the development of MCI. Results: The prevalence of MCI increased with increasing GGT level, from the lowest quartile to the highest quartile of GGT: 8.4% (66/786), 14.2% (119/840), 17.6% (108/613), and 21.4% (151/704), respectively. At the same time, as GGT levels increased, so did the risk of MCI. In the fully adjusted model, compared with those for participants in the lowest GGT quartiles, the odds ratios (ORs), and 95% confidence intervals (CIs) for MCI for participants in the second, third, and fourth GGT quartiles were 1.49 (1.04–2.12), 1.53(1.06–2.21), and 1.88 (1.33–2.65), respectively. The risk of developing MCI was further increased in people with high GGT levels who were obese (OR = 1.96, 95% CI: 1.39–2.76, P < 0.001), slept less (OR = 1.91, 95% CI: 1.35–2.71, P < 0.001), had high levels of uric acid (OR = 1.55, 95% CI: 1.03–2.32, P < 0.001), or after menopause (OR = 2.92, 95% CI: 2.07–4.12, P < 0.001). Conclusion: We found that MCI is more common in women with elevated GGT levels, so GGT could be a potential diagnostic marker for MCI. Meanwhile, our findings indicated that women with high GGT levels had an increased risk of MCI when they were obese, sleep deprived, had high serum uric acid (SUA) levels or underwent menopause.